Genetic and ecological characterization of the giant reed (Arundo donax) in Central Mexico - Ricardo Colin; Erika Aguirre-Planter; Luis E. Eguiarte (PLoS ONE, 2025)
Arundo donax (giant reed) is currently found in all tropical-subtropical and warm-temperate areas of the world. In Mexico, A. donax is a common introduced species, growing in a variety of climates and habitats. We used Inter Simple Sequence Repeats (ISSRs) markers to analyze 20 populations across different geographic regions of Mexico to estimate the geographic structure of its genetic variation, the levels of clonal diversity, and their predominant reproductive mode (clonal vs. sexual), and to explore environmental factors that may be related to genetic differentiation. In addition, we used bioclimatic variables to perform multivariate statistical analyses. We detected a total of 77 different genotypes, finding that all the analyzed populations are multiclonal (including from 3 to 9 different genotypes). The data suggest that sporadic sexual reproduction takes place in some populations. We found four main genetic groups and low levels of gene flow among clusters. Ecological characterization analyses indicate that the distribution and abundance of genotypes is structured and influenced by environmental factors, supporting the existence of three main ecological-genetic groups in Mexico (Central Highlands, Coasts, and North).